Editorial: acknowledging our past - Vosloo, Robert (Stellenbosch theological journal, 2022)
Who do you say we are? In July 1822, Andrew Murray Sr, from Scotland, arrived in South Africa to serve as a minister in the DRC congregation of Graaff-Reinet, and in 1825 he married the young Maria Susanna Stegmann. It is noteworthy that, whereas Andrew Murray Sr came to the Cape 200 years ago, the family of the materfamilias, Maria Susanna Stegmann, can be traced back to Paul Roux, who was one of the Huguenot Refugees, driven from France by the revocation of the Edict of Nantes - thus retracing the family roots on the mother’s side to their arrival in the Cape in 1688, 334 years ago!